Adverse Childhood Experiences: The Protective and Therapeutic Potential of Nature - Touloumakos, Anna K.; Barrable, Alexia (Frontiers in Psychology, 2020)
Adverse childhood experiences (ACEs) are prevalent in many western populations. Large studies have put the likelihood of having at least one ACE above 50% of the general population. ACEs and the associated experience of chronic stress, moreover, have been consistently linked with a variety of negative physical and psychological health outcomes across the lifespan from behavioural problems and cognitive difficulties early on, to greater chance of suffering from a mental health disorder and engaging in self destructing behaviours. The literature puts forward several protective factors, such as mother-child relations, parental health and community engagement. In this perspective paper we put forward the potential of regular nature engagement as a possible additional protective factor. Nature’s therapeutic potential has been well documented, for many psychopathologies and mental health difficulties. Yet studies looking at the protective and therapeutic potential of nature with people with ACEs are remarkably limited in numbers. In this perspective piece we conduct a search of the literature to find previous applications of nature as a protective or therapeutic intervention for people with ACEs. We highlight the gap in the current literature, and put forward various mechanisms of action that justify a closer exploration of this area in further research.